2001
DOI: 10.1055/s-2001-16520
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Placebo-Controlled Trial of Prednisone and Allopurinol in the Prevention of ERCP-Induced Pancreatitis

Abstract: Neither prednisone nor allopurinol showed a beneficial influence on the incidence and severity of post-ERCP pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
1
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 20 publications
1
79
1
3
Order By: Relevance
“…The histological abnormalities in the combined treatment group were significantly less compared with the use of allopurinol and HBO alone, indicating a potentiation of effect. Allopurinol also decreased the oxidative stress parameters, as it has been reported previously [13,14,27,28] , although allopurinol was found to have no effect on the incidence and severity of endoscopic retrograde cholangiopancreatography (ERCP)-induced pancreatitis in studies on human subjects by Budzynska et al [29] . When allopurinol was co-administered with HBO at the same doses, the overall antioxidant effect did not increase.…”
Section: Discussionsupporting
confidence: 58%
“…The histological abnormalities in the combined treatment group were significantly less compared with the use of allopurinol and HBO alone, indicating a potentiation of effect. Allopurinol also decreased the oxidative stress parameters, as it has been reported previously [13,14,27,28] , although allopurinol was found to have no effect on the incidence and severity of endoscopic retrograde cholangiopancreatography (ERCP)-induced pancreatitis in studies on human subjects by Budzynska et al [29] . When allopurinol was co-administered with HBO at the same doses, the overall antioxidant effect did not increase.…”
Section: Discussionsupporting
confidence: 58%
“…Moseler and colleagues, in another large-scale trial found no statistical difference in the frequency of PEP in patients given allopurinol (13%) compared with those given a placebo (12%) [112] . Budzynska et al [106] reported similar rates of pancreatitis in 200 patients who received either allopurinol (12%) or placebo (8%). If one was to pool the results of all 3 studies in a crude metaanalysis, total rates of pancreatitis in the allopurinol groups (62 of 579, 10.7%) and the placebo groups (71 of 565, 12.6%) are not statistically different.The allopurinol dosage and the timing of administration differ among all 3 studies: 600 mg at 15 and 3 h before ERCP in the Katsinelos study, 600 mg at 4 h and 300 mg 1 hour before ERCP in the Mosler study, and 200 mg at 15 h and 3 h before ERCP in the Budzynska study.…”
Section: Category 3: Markers Of Systemic Inflammationmentioning
confidence: 76%
“…Two studies (without adjustment for confounding variables or multivariate analysis) suggested that corticosteroids might be protective [104,105] . Subsequently, 5 randomized controlled trials with large numbers of patients demonstrated no benefit, nor any trend toward a benefit, for various corticosteroid formulations, including methylprednisolone, hydrocortisone, and prednisone [106][107][108][109][110] . In a similar approach, it was hoped that xanthine oxidase inhibitors, such as allopurinol, might prevent PEP by inhibiting generation of oxygen-derived free radicals.…”
Section: Category 3: Markers Of Systemic Inflammationmentioning
confidence: 99%
“…For example, in a study by Augustin et al (1994) in uveitis, a dose of allopurinol that was effective in blocking XO activity failed to affect the course of the disease, whereas higher doses of the compound (at which antioxidant effects become more prominent) proved effective in reducing the inflammation. The attempts to use allopurinol for anti-inflammatory purposes at the bedside have also failed so far: in a 300-patient study on pancreatitis developing as a complication of endoscopic retrograde cholangiopancreatog-THERAPEUTIC EFFECTS OF XANTHINE OXIDASE INHIBITORS raphy, allopurinol was found to be clinically ineffective (Budzynska et al, 2001).…”
Section: F Xanthine Oxidase and Inflammatory Bowel Disease And Othermentioning
confidence: 99%